Capacity and Performance Assessment of Wurukum Roundabout in Makurdi Metropolis: A Comparative Study using ARCADY and SIDRA INTERSECTION Software - Adeke, P. T.; Etika, A.; Atoo, A. A. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2020)
Following the recent public outcry over delays and long queues at the Wurukum Roundabout Makurdi due to increase in travel demand at the road intersection, it is not certain if the performance of the roundabout is satisfactory based on engineering specifications and judgment. Therefore, simulation of the 5-arm at-grade intersection was carried out using Assessment of Roundabout Capacity and Delay (ARCADY) and the Signalised (and unsignalised) Intersection Design and Research Aid (SIDRA INTERSECTION) Software. The geometric dimensions of the roundabout were measured and manual traffic counts were used to obtain average travel demand matric from the morning (8:30 – 9:30 am) and evening (4:30 – 5:30 pm) peak periods, and heavy vehicle proportion of Origin-Destination (O-D) flows on the roundabout. Simulation models of the Wurukum roundabout were built using ARCADY and SIDRA INTERSECTION software to measure its capacity and performance based on key parameters such as Level of Service (LOS), average geometric delay and queue length among others. Though significant variations were observed among estimated performance indices, results obtained from the simulated models and statistical analysis (test of hypothesis using Chi-square test) indicated that the roundabout operates at failed state classified as LOS F at its present condition. Recommended strategies to improve the capacity and performance of the roundabout included any of the following; construction of a fly-over bridge connecting the Northern and Southern approaches as permitted by site physical features, signalisation of the roundabout with traffic signs, proper pavement markings and adjustment of its geometric features, or redesign and construction of road network within Makurdi metropolis to divert and reduce traffic demand on the roundabout.